Study of Passive Evaporative Cooling Technique on Water-retaining Roof Brick. (2017) - Han, Rubing; Xu, Zhimao; Qing, Yutao
Abstract: This paper introduces a new method water-retaining roof brick to reduce the energy cooling load in meeting people's comfort demands in hot seasons. An experimental model of passive evaporation is designed in order to explore a complete heat transfer process law of water-retaining brick in hot summer and cold winter region. The result of using a flat roof with water-retaining brick shows a drop of 1.9 °C in the indoor temperature in summer compared to the base case of the conventional flat roof in residential buildings. In addition, the results indicate the cooling load required for the building will decrease after using water-retaining bricks on roof and also using the radiation shield on roof. The best solution to increase the indoor thermal comfort is water-retaining brick rather than roof with shield, because the evaporation process plays a supporting role to ease the city heat island effect. Thus, it's the most optimal scheme.